Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 3 - Differentiation - 3.8 Implicit Differentiation - Exercises - Page 152: 27


$$ y'(x)= 1-2x $$

Work Step by Step

Given $$ x+y x^{-1}=1\ \tag{1}$$$$ y=x-x^{2} \tag{2}$$ From (1), multiply by $x$ \begin{align*} x+y x^{-1}&=1\\ x^2+y&=x\\ y&= x-x^2 \end{align*} which is the same as the second equation. Differentiating (1), we get \begin{align*} 1-y x^{-2}+x^{-1} y^{\prime}&=0\\ y'(x) &= \frac{y x^{-2}-1}{x^{-1}}\\ &= y x^{-1}-x \end{align*} Put (2) in the last equation to get $$ y'(x)= 1-2x $$ which is the derivative of the second equation.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.